Zein's Personality Archetype: A Study of Carl Jung's Analytical Psychology in Said Ramadhan El-Bouthy's Novel Mamo Zein - Istianah,; Shofiyuddin, Haris (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to reveal the personality archetypes of Zein in Said Ramadhan El-Bouthy's novel Mamo Zein using Carl Gustav Jung’s literary psychology approach. The central issue examined is the discord between palace social demands and the character's personal desires. Using a descriptive qualitative method and note-taking technique, the study finds that Zein’s personality is shaped by four archetypes: Persona as a social mask of a princess; Shadow as inner turmoil affecting her physical state; Animus as rational courage in disguise; and Self as the center of spiritual integration. The study concludes that through the process of individuation, Zein achieves psychological harmony as a response to the pressures of reality and authority.